Behavior of Mortality in Cienfuegos Province in the Period 2013-2022 - Jorge Enrique Portell del Sol; Dania Lázara Pedraza Alejo; Yusimí Alejo Padrón; Leticia Castro Morejón; Ling Denisse Santeiro Pérez; Yaniela Sarmiento Albelo (Revista Finlay, 2024)
Foundation: in the last two decades there has been an increase in mortality in the world, caused mainly by chronic non-communicable diseases that cause a serious health problem. Objective: to characterize mortality in the Cienfuegos province during the period 2013-2022. Method: a descriptive, retrospective cross-sectional study was carried out in health systems and services, which analyzed all deaths (N=39,684) in the period 2013-2022, grouped by five-year periods 2013-2017 and 2018-2022 according to variables. selected clinical and epidemiological conditions, municipality of residence, place of death, basic cause of death, general and premature mortality rates. The data were obtained from the MortaPro and Mortagen automated system, from the provincial department of medical records and statistics. Annual and five-year rates were calculated. Arithmetic mean and standard deviation were used. Results: there was an increase in the provincial general mortality rate by 27.9 % and premature mortality by 20.3 % in the last 5 years; the 8 municipalities showed an increase, with the highest rates: Cumanayagua, Rodas and Abreus. In the five-year period 2018-2022, the mortality rate increased in both sexes, with males predominating. The home predominated as the place of death. Heart diseases led mortality in both five-year periods, followed by malignant tumors, both accounting for 59.0 % of deaths. Conclusions: there was an increase in the provincial general mortality rate and premature mortality in the last 5 years; the 8 municipalities show an increase. In the five-year period 2018-2022, the mortality rate increased in both sexes, with males predominating. The home predominates as the place of death. Heart diseases lead mortality in both five-year periods, followed by malignant tumors.